Prevalence of hypertension and its associated factors among primary school students in federal territory - Saeed, Ghaloo Sobia (2021)
Hypertension is an important risk factor for cardiovascular disease, and there is an increasing risk of developing hypertension among children. Our study aims to determine the prevalence of hypertension and its associated factors among primary school children (7 to 12 years) in the Federal territory. A self-administered questionnaire was used that explores the sociodemographic background, past medical history, family history & lifestyle characteristics of the participants. Diagnosis of hypertension was based on standard protocol. Data analysis was done using SPSS v26.0. This study involved 251 respondents. The prevalence of hypertension among primary school children is 2%. Significant determinants of hypertension were higher body mass index (BMI), marital status, children who lived with a single parent and of Indian ethnicity. In multivariate logistic regression analysis, it was found that Indians had 55 times higher odds of having true hypertension compared to Malays (95%CI =1.47-2061.87, p = 0.03). It was also found that children from households with a single parent had 85 times higher odds of having true hypertension compared to households with both parents (95%CI = 2.68-2537.53, p = 0.01). Furthermore, those with a higher BMI had 1.4 times higher odds of having true hypertension (95%CI = 1.06-1.43, p = 0.018). The prevalence of hypertension is similar the rates reported around the world. This provides information on where regular monitoring of BP in children should be advocated among healthcare professionals, especially among children with risk factors such as obesity for the development of hypertension.